Forced inactivity and barriers to participation among refused asylum seekers - Jon Burnett (PAFRAS Briefing Paper Number 12, 2009)
PAFRAS Briefing Paper 12 focuses on the ‘deskilling’ of refused asylum seekers. Asylum seekers are prevented from working in the UK except where there are extenuating circumstances, and if a claim for asylum is refused then this denial of work is continued. At all stages of the asylum process an individual is forced into a form of limbo, with opportunities for employment and education limited both formally and informally.